Peningkatan Nafsu Makan Balita Melalui Kombinasi Pijat Tui Na Dan Hypnoparenting Di Kelurahan Habaring Hurung Wilayah UPT. Puskesmas Tangkiling - Hanovani, Hanovani; Yuliana, Fitri; Kurniawati, Darini (Akademi Kebidanan Bunga Husada Samarinda, 2023)
Background: Eating difficulties are very common in children aged 1-5 years. At this age, poor eating habits mean that children tend not to eat or have a decreased appetite, this can lead to decreased nutritional status and stunted growth and development of children. Objective: To determine the increase in toddlers' appetite through a combination of Tui Na massage and Hypnoparenting in the Habaring Hurung Village, UPT area. Tangkiling Health Center. Methods: The research design is a quasi experiment with a non-random pre-test post-test design. The population in this study were toddlers in Habaring Hurung Village, the sample was toddlers who had less appetite. The sample was obtained by purposive sampling using the sampling technique according to Creswell's theory, so that there were 15 respondents in the experimental group and 15 respondents in the control group. Data collection used appetite questionnaires and observation sheets and statistical analysis used unpaired parametric t-test. Results: After applying the combination of Tui Na massage and Hypnoparenting by toddler mothers for 7 days, it was found that the P Value < Alpha (0.012 < 0.05). Conclusion: So it can be concluded that there is a significant difference between the results of measuring appetite after being given treatment to the respondent variables who have done Tui Na Massage and Hypnoparenting on Toddlers.